Psychometric Features of Patient Health Engagement Scale in Iranian Breast Cancer Patients - Maryam Changizi; Niloofar Ahmadloo; Mohammad Hossein Kaveh; Leila Ghahramani (Shiraz University of Medical Sciences, 2023)
Background: Breast cancer is one of the most prevalent cancers among women worldwide. The phe scale is the first credible measurement tool to delve into critically ill patients' experiences and emotional state and detect their level of engagement in the treatment and care process. However the Persian version of the scale needs to be further investigated. Accordingly, the present study aimed to evaluate the psychometric features of the patient health engagement scale (phe s) in Iranian patients suffering from breast cancer.Methods: This is a cross-sectional study. The sample size was estimated by multiplying the total number of items by ten. The sample size was estimated for this 5-item scale 128 breast cancer patients who referred to a specialized clinic in 2020. Content validity and reliability analysis were performed, and the data were analyzed using IBM SPSS26 software and R content validity package.Results: The ordinal alpha of thesample was 0.626, indicating an acceptable internal consistency. The analysis of the rash model revealed an acceptable infit and outfit MNSQ (685-932). The polychoric correlation coefficient within the items was 46, representing a moderate correlation. All the factor loadings had a high value (0>60), thereby confirming the single dimensionality of the scale.Conclusion: The phe scale has favorable reliability and validity to assess the patients' emotional adjustment and their engagement in their health and self-management before designing and implementing any intervention.